Realtime android-based firewall management system / Muhammad Nur Hakim Norizman - Norizman, Muhammad Nur Hakim (2020)
This project is about the effectiveness and practicality of remote connection for firewall management system using android platform. It has been long known that firewall is the most important device that acts as a first layer of defence for the network but not many firewalls provides remote connection and monitoring via a mobile phone. All there is just a web-based management system for users to implies policies and rules This project will use the android-based platform to create an application or software that uses a remote connection and monitoring of a firewall. This project will enable users and admins to connect and monitor firewall remotely if it is in the same network. The method used is by implementing an already existing application template and system and combines multiple methods to make the functionality more efficient. The system is then translated into android-based software which uses flutter to run. The system will be tested via mobile phone that is connected to the same Wi-Fi network and then will try to connect to the firewall and execute functions. The recent findings are that many of the firewall existed nowadays have the potential threat towards evolving cybersecurity attacks which may lead to network intrusion, data leaks, and personal data theft. To prevent from such things from happening, the firewall must be at the most efficient and high in terms of security and manageability.